Enhanced photocatalytic activity of hierarchical C/ZnO nanocomposite derived from solvothermally restructured Zn-BTC microspheres. Issue 3 (June 2022) - Sharma, Kajal; Kaushik, Ravinder; Pandey, Pawan Kumar; Chowdhury, Sumanta; Gogoi, Rituporn; Singh, Astha; Halder, Aditi; Siril, Prem Felix
Abstract: Single step solvothermal synthesis of hierarchical and hollow microspheres (HHMs) assembly of 1D zinc-trimesic acid (Zn-BTC) MOF nanospikes, without using any external stabilizer as shape modifier is reported here. Detailed electron microscopy imaging revealed that the Zn-BTC HHMs form through a self-templating mechanism due to the typical reaction conditions. The Zn-BTC HHMs were annealed to form ZnO/C hierarchical nanocomposite microspheres (HNMs). HNMs were found to be quite active for the photocatalytic water remediation through the photo-oxidation of dyes as well as photo-reduction of Cr (VI). Thorough characterization revealed that the HNMs exhibited three-dimensional (3D) hierarchical morphology with comparatively higher mesoporosity, extended visible light absorption, and better separation of photogenerated charges (e - /h + ), resulting in enhanced photocatalytic performance (0.40 and 1.89 mg·g −1 ·min −1 removal efficiency for MV and Cr (VI) respectively). The enhanced photocatalytic activities of the HNMs were found to be due to the synergism between carbon matrix and the well-dispersed ZnO quantum dots. Graphical Abstract: ga1 Highlights: Hierarchical and hollow microspheres were formed from Zn-BTC MOF nanospikes. The microstructures were prepared using a template-free and surfactant-free method. Annealing the microstructure yielded ZnO/C hierarchical nanocomposite microspheres. The nanocomposite formed under N2 contained ZnO nanodots supported on carbon. The nanocomposite was found to be excellent photocatalyst for environment remediation.